An epidural steroid injection in the 6 months preceding a lumbar decompression without fusion predisposes patients to postoperative infections - Donnally III, Chester J.; Rush III, Augustus J.; Rivera, Sebastian; Vakharia, Rushabh M.; Vakharia, Ajit M.; Massel, Dustin H.; Eismont, Frank J. (Journal of Spine Surgery; Vol 4, No 3 (September 14, 2018): Journal of Spine Surgery, 2018)
Background: To determine if the timing of a lumbar epidural steroid injection (LESI) effects rates of post-operative infection in patients receiving a non-fusion lumbar decompression (LDC) due to degenerative disc disease (DDD). Lumbar pain due to DDD can frequently be temporized or definitively treated with epidural injections. While there is ample literature regarding the infection risks associated with corticosteroid injections prior to hip/knee replacements, there are few studies relating to the spine. Methods: A nationwide insurance database was queried to identify those who underwent LDC for DDD without instrumentation [2005–2014]. Lumbar fusion procedures were excluded. From this group those with a history of a LESI were identified and matched to a control group without a history of LESI. Four separate cohorts were examined: (I) LDC and no LESI within 6 months (control); (II) LDC performed within 0–1 month after LESI; (III) LDC between 1 and 3 months after LESI; (IV) LDC performed between 3 and 6 months after LESI. Results: There was an increased odds of a 90-day postoperative infection if the LESI was within the 1–3 months (OR =4.69; P